Determinant Factors Influencing Islamic Entrepreneurial Intentions : Perspectives of State Islamic Religious Universities Students in Jember Regency - Fiqih Hidayah Tunggal Wiranti; Novita Nurul Islami; Anita Tri Widiyawati; Widyo Pramono (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2023)
Entrepreneurship education efforts are being carried out by educational institutions, including Islamic Universities. State and private Islamic tertiary institutions are responsible for preparing their students to become excellent entrepreneurs. Therefore this study aims to explore how the influence of entrepreneurial knowledge and entrepreneurial motivation as a determinant factor on Islamic Entrepreneurial Intention both simultaneously and partially. This research was conducted on students of UIN Kiai Haji Achmad Siddiq Jember. The population in this study was 1,700 students, and a sample of 195 students was taken with the criteria of having taken the Entrepreneurship course. The method used in this research is descriptive quantitative. Data collection was done using a questionnaire, while data analysis used SPSS 25.0. From the study carried out, it was found that partially entrepreneurial knowledge and entrepreneurial motivation had a significant effect on Islamic Entrepreneurial Intention with the results of sig 0.000 t-statistics 3.877 and sig 0.000 t-statistics 10.144. Meanwhile, simultaneously entrepreneurial knowledge and motivation significantly affect Islamic Entrepreneurial Intention with sig 0.000 f-statistics 171.646. Based on the results, it was found that entrepreneurial knowledge has a lower influence, so recommended that there be innovations in entrepreneurship learning mainly related to Islamic Entrepreneurs in Islamic Higher Education.